The Effect of Using Different Types of Honey As Sugar Substitute on the Quality of Milk Jelly Candy - Faradisa Zul Alfi Husna; Dedes Amertaningtyas (Journal of Agriprecision & Social Impact, 2025)
This study investigates about the effect of using different types of honey (coffee honey, randu honey and multiflora honey) on the quality of cow's milk jelly candy. Specifically, the resrarch examines the reducing sugar (%), water activity (Aw) and organoleptic (aroma, taste and color). The research method used a laboratory experiment with Completely Randomized Design (CRD) with four treatments and four replications. The treatments included P0 = using sugar 25%, P1 = using coffee honey 25%, P2 = using randu honey 25% and P3 = using multiflora honey 25%. Data analysis was carried out by Analysis of Variance (ANOVA). If different results were obtained between treatments. Duncan’s Multiple Range Test (DMRT) was continued. The results of the study showed that the use of different types of honey (coffee honey, randu honey and multiflora honey) gave a very significant effect (P <0.01) on the organoleptic taste and color, and reducing sugar (%) but did not give any effect on the organoleptic aroma and water activity (Aw).Rreducing sugar is 17.44-3.49%; water activity (Aw) is 0.87-0.84; organoleptic aroma 3.42-3.83, taste 4.25-3.6, color 4.50-3.33.